COMPARATIVE ANALYSIS OF LEXICAL UNITS IN CHARACTERS' SPEECH (based on translations of the novel "Navoi") (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article compares the speech culture of the characters of the work on the basis of the original novel "Navoi" published in 1944 by the famous Uzbek writer Musa Tashmuhammad Aibek and the English translation by I. Tokhtasinov and O.Mominov. Since the novel was translated into English from Russian, the Russian translations of M.Sale in 1945 and P.Slyotov in 1946 were also studied. The work was translated into French in 1948 by the French translator A.Oran. The French version is also studied in a comparative analysis.